Whole body mass estimates and error propagation in countermovement jump: a simulated error study - Burnett, J. K.; Kim, Y.-W.; Kwon, H. J.; Miller, R. H.; Shim, J. K. (Sports Biomechanics, 2023)
High-velocity actions are central to clinical and athletic performance, with jumping used to assess outcomes in sports medicine. Ground reaction force (GRF)-based methods are the standard for computing jump characteristics, but require mass estimation and GRF integration, potentially resulting in mass errors which influence outcomes. This study investigated how simulated mass errors influenced the centre of mass (CoM) trajectory during a countermovement jump. The mass was estimated from the static GRF, and simulated errors were added or subtracted to the mass. The CoM trajectory with simulated mass errors was computed using the GRF-based method to investigate mass mis-estimation`s influence on jump height. A regression model indicated that, for a 1 kg mass change, there was a 7.7 cm jump height change, and the jump height differed by 11.5 ± 0.4 cm from the maximum to minimum error. A 2-way ANOVA identified significant height differences between the starting position, and landing, or final position with mass errors of ± 0.2 or ± 0.4 kg. These results reveal that small mass errors may produce inaccurate conclusions regarding performance changes, and that errors may propagate throughout the jump trajectory. Caution may be necessary when using GRF-based methods to compute jump height as a power proxy.